1997
DOI: 10.1074/jbc.272.16.10817
|View full text |Cite
|
Sign up to set email alerts
|

The Condensation of Chromatin in Apoptotic Thymocytes Shows a Specific Structural Change

Abstract: Chromatin condensation and DNA cleavage at internucleosomal sites have been recognized early as hallmarks of apoptosis, and it has been suggested that extensive DNA chain scission could directly result in the formation of dense chromatin bodies. Here we have shown that no causal relationship exists between DNA degradation and chromatin condensation in glucocorticoid-induced thymocyte apoptosis. The chromatin rearrangement occurred independent of as well as prior to DNA cleavage and involved a specific conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 24 publications
3
33
0
1
Order By: Relevance
“…Due to the observed correspondence of apoptotic nuclear condensation (Allera et al, 1997) and subsequent nuclear fragmentation with changes in ultrasound images, we hypothesized that the nuclear material in the cells was responsible for the increased ultrasound backscatter. This hypothesis was tested using the same cell culture system, but with the pharmaco-active agent colchicine (Dustin, 1980), which resulted in condensed nuclear material in the form of metaphasic chromosomes, but not fragmentation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the observed correspondence of apoptotic nuclear condensation (Allera et al, 1997) and subsequent nuclear fragmentation with changes in ultrasound images, we hypothesized that the nuclear material in the cells was responsible for the increased ultrasound backscatter. This hypothesis was tested using the same cell culture system, but with the pharmaco-active agent colchicine (Dustin, 1980), which resulted in condensed nuclear material in the form of metaphasic chromosomes, but not fragmentation.…”
Section: Resultsmentioning
confidence: 99%
“…Some 25 million of the protein units in combination with 2 m of DNA are packed into chromosomes which are approximately 6-8 µm in length when condensed (van Holde, 1988). The process of nuclear condensation, which takes place in the early stages of apoptosis (Allera et al, 1997), similar to mitosis, compacts chromosomes from forms which are distributed throughout most of the cell's nucleus to more canonical condensed forms. Other previous studies also support the postulate that the cellular nuclear material is the major scatterer of high frequency ultrasound (Bérubé et al, 1992;Hunt et al, 1995;Czarnota et al, 1997a).…”
Section: Discussionmentioning
confidence: 99%
“…Using inhibitors or activators of protein kinases, apoptosis can be induced by staurosporine without considerable histone phosphorylation (48) or with H3 phosphorylation by gliotoxin, a protein kinase A activator (51). It was reported that histone H3 and H4 were deacetylated in rat apoptotic thymocytes (52). It would be of interest to ascertain the change in apoptotic histone acetylation under the influence of the caspase inhibitor, Z-Asp-CH 2 -DCB.…”
Section: Discussionmentioning
confidence: 99%
“…Differential scanning calorimetry (DSc) is a relatively fast thermal technique that provides data on physical and energetic properties of cellular structures/compounds (19)(20)(21). earlier, it was documented that this method could be useful for the monitoring of native chromatin in cell nuclei (19).…”
Section: Relationship Between In Vitro Drug Sensitivity and Clinical mentioning
confidence: 99%